Axial compressive performance of concrete-filled UHPC tubular columns reinforced with self-prestressed Fe-SMA spiral stirrups - Chushi Cui; Zhiqiang Dong; Yifan Zhao; Tianhao Han; Yichuan Zheng; Yijie Pan; Elyas Ghafoori (Case Studies in Construction Materials)
This study investigates the axial compressive behavior of an innovative composite column comprising a prefabricated ultra-high performance concrete (UHPC) tube reinforced with self-prestressed iron-based shape memory alloy (Fe-SMA) spiral stirrups and cast-in-place ordinary concrete. Embedding Fe-SMA spirals within UHPC tubes during autoclave curing simultaneously activates the self-prestressing effect, enhancing UHPC’s mechanical properties and imposing active circumferential confinement. Experimental tests were conducted on 24 specimens to evaluate the effects of Fe-SMA prestress levels, stirrup spacing, and curing methods. Results revealed that the self-prestressed Fe-SMA reinforced composite columns exhibited superior axial load-bearing capacity (up to 3694 kN), elastic modulus and ductility compared to non-prestressed counterparts. The self-prestressed Fe-SMA spirals effectively mitigate the inherent brittleness of UHPC, delay crack propagation, and promote strain-softening behavior. Compared to non-prestressed Fe-SMA-confined specimens, the compressive deformation capacity and hoop stiffness are improved by 28.15 % and 15.77 %, respectively. Notably, reducing Fe-SMA stirrup spacing effectively enhances confinement efficiency, while autoclave curing improves compressive strength by 17–31 % over natural curing. A calculation method is proposed to predict the ultimate load-bearing capacity of the composite columns, which closely matches experimental results, with errors below 10 %. This research validates the feasibility of the proposed composite system, offering a cost-effective and durable solution for prefabricated structural columns in marine and cross-sea bridge engineering.